Printing feed liquid as well as preparation method and application thereof in printing and dyeing

By using modified acrylic emulsions and rare earth-doped nano-TiO2 in the printing material liquid, the problems of inconspicuous colors and unclear patterns of traditional printing material liquids are solved, and the color fastness and pattern brightness of printed fabrics are improved, and the color fastness and pattern brightness of printed fabrics are extended. It provides service life and enhances friction and wash resistance.

CN119321061AActive Publication Date: 2025-01-17GUANGZHOU YABAO PRINGTING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411651454.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-17
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

During the preparation and use of traditional printing liquids, there are problems such as dyes that are easy to diffuse, uneven penetration, unclear printing patterns, and insufficient bright colors, which are difficult to meet the market's demand for color brightness, pattern clarity and production efficiency.

Method used

Using modified acrylic emulsion as the basis, a new printing liquid was prepared by adding rare earth doped nano-TiO2, silane coupling agent and other components, which used the high chemical stability of titanium dioxide and the optical properties of rare earth elements to form chemical bonding and Complexes improve the adsorption and diffusion properties of dyes, enhance color fastness and pattern vibrancy.

Benefits of technology

It achieves the brightness and color fastness of the printing pattern, extends the service life of the printed fabric, enhances the color fastness of friction and water-resistant, and ensures the durability and stability of the printing effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005142001490000141
    Figure BDA0005142001490000141
  • Figure BDA0005142001490000151
    Figure BDA0005142001490000151
Patent Text Reader

Abstract

The invention relates to the technical field of textile printing and dyeing, in particular to printing feed liquid, a preparation method thereof and application of the printing feed liquid in printing and dyeing. The printing material liquid is prepared from the following raw materials in parts by weight: 60 to 70 parts of modified acrylic emulsion, 2 to 2.4 parts of thickening agent, 0.5 to 1.5 parts of dispersing agent, 4 to 5 parts of stabilizing agent, 0.5 to 1 part of humectant, 1 to 2 parts of curing agent, 0.2 to 0.4 part of defoaming agent, 3 to 5 parts of dye and 50 to 60 parts of water. The printing material liquid prepared by the invention can be used for remarkably improving the quality of printed patterns and enhancing the color fastness to rubbing and the color fastness to washing of printed fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textile printing and dyeing, and in particular to a printing liquid and a preparation method thereof and application in printing and dyeing. Background Art

[0002] As an important part of the textile printing and dyeing industry, printing technology has been developing and innovating for a long time. Although traditional printing methods, such as manual screen printing and roller printing, have met market demand to a certain extent, they still have many shortcomings in terms of color vividness, pattern clarity and production efficiency. With the advancement of science and technology and the enhancement of environmental awareness, the development of a new printing liquid and its preparation method, and the exploration of its application in printing and dyeing have become important topics in the textile printing and dyeing industry.

[0003] The preparation of traditional printing liquid generally involves the mixing of multiple dyes, auxiliaries and thickeners. The selection and proportion of these ingredients directly affect the printing effect. However, there are some problems in the preparation and use of traditional printing liquid, such as easy diffusion of dyes, uneven penetration, unclear printing patterns, and insufficiently bright colors. Based on this, the present invention provides a printing liquid and a preparation method thereof and an application thereof in printing and dyeing. Summary of the invention

[0004] The purpose of the present invention is to provide a printing liquid and a preparation method thereof and application in printing and dyeing, so as to solve the above-mentioned technical problems, improve the quality of printing patterns, and also enhance the color fastness to rubbing and washing of printed fabrics.

[0005] On the one hand, the present invention provides a printing liquid, comprising the following raw materials in parts by weight: 60-70 parts of modified acrylic emulsion, 2-2.4 parts of thickener, 0.5-1.5 parts of dispersant, 4-5 parts of stabilizer, 0.5-1 part of humectant, 1-2 parts of curing agent, 0.2-0.4 parts of defoaming agent, 3-5 parts of dye and 50-60 parts of water.

[0006] Furthermore, the preparation method of the modified acrylic emulsion includes: mixing acrylic acid, methyl methacrylate, and n-butyl acrylate monomers with deionized water, adding sodium dodecyl sulfate and nonylphenol polyoxyethylene ether and continuing to stir to obtain a mixed solution, then adding rare earth-doped nano-TiO2 for ultrasonic dispersion for 30-40 minutes, gradually heating to 75-79°C, adjusting the pH to 4-6, then adding ammonium persulfate, heating to 82-84°C, keeping the temperature for reaction for 4-5 hours, then cooling to room temperature, and adjusting the pH to 8 with ammonia water.

[0007] Furthermore, the weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, rare earth-doped nano-TiO2 and ammonium persulfate is (2-3): (12-14): (20-22): (40-50): (0.5-1): (1-1.2): (0.2-0.4): (4-5).

[0008] Furthermore, the preparation method of the rare earth-doped nano-TiO2 includes: dispersing the silane coupling agent KH-550 in an ethanol aqueous solution by ultrasonic for 120-140 minutes, adjusting the pH to 3-4 with glacial acetic acid to obtain a silane coupling agent solution; adding the nano-TiO2 to anhydrous ethanol and ultrasonically dispersing it for 50-70 minutes, adding cerium nitrate, and slowly dripping the silane coupling agent solution, adjusting the pH to 9-10 with ammonia water, heating to 65-75°C and stirring the reaction for 2-2.2 hours, cooling, centrifuging, washing with water and then drying to obtain the product.

[0009] Furthermore, the weight ratio of the silane coupling agent KH-550, ethanol aqueous solution, nano-TiO2, anhydrous ethanol and cerium nitrate is (6-8): (30-40): (25-35): (15-20): (4-5).

[0010] Furthermore, the mass ratio of water to ethanol in the ethanol aqueous solution is 1:1.

[0011] Furthermore, the thickener is ACRACONC FN 01.

[0012] Furthermore, the dispersant is Dispers740W.

[0013] Furthermore, the stabilizer is sodium citrate.

[0014] Furthermore, the moisturizing agent includes at least one of urea, ethylene glycol, and glycerin.

[0015] Furthermore, the curing agent includes ARADUR38-1 or ARADUR3986.

[0016] Furthermore, the defoaming agent is Z-2875.

[0017] On the other hand, the present invention also provides a method for preparing printing liquid, the steps comprising: adding a defoamer, a dispersant, a humectant, a stabilizer and water to a modified acrylic emulsion in sequence while stirring, and stirring and dispersing; then adding a thickener, a curing agent and a dye, and stirring and dispersing evenly.

[0018] On the other hand, the present invention also provides the application of the printing liquid in fabric printing and dyeing.

[0019] The beneficial effects of the present invention are:

[0020] The invention utilizes the high chemical stability of titanium dioxide to achieve its long-term stability in the modified acrylic emulsion. The introduction of titanium dioxide enables the modified acrylic emulsion to have a stronger ability to absorb and reflect ultraviolet rays, thereby reducing the destructive effect of ultraviolet rays on the printing liquid, which helps to maintain the vividness and color fastness of the printed pattern and prolong the service life of the printed fabric. In addition, titanium dioxide can form a chemical bond with the acrylic resin, which is not easy to fall off or wear, thereby improving the color fastness of the printing liquid.

[0021] In the present invention, rare earth-doped nano-TiO2 is used to modify acrylic emulsion. The doping of rare earth elements may change the optical properties of titanium dioxide, thereby affecting its coloring performance; the rare earth element cerium has a special electronic structure and chemical activity, and can form a complex complex with dye molecules, thereby increasing the dyeing percentage of the dye; in addition, the doping of rare earth cerium may also improve the adsorption and diffusion properties of the dye on the fiber, making the printed pattern more vivid and the color purer.

[0022] In the present invention, silane coupling agent KH-550 is further added on the basis of rare earth doped nano-TiO2, so as to improve the adhesion and dispersibility of the material on the fiber surface, and the modification treatment helps to reduce the shedding and fading of the dye during the washing process, thereby enhancing the washing resistance and color fastness of the printed fabric. In addition, the silane coupling agent can also improve the interaction between the fiber and the dye, making the printed pattern more durable and stable.

[0023] The invention uses rare earth doped nano-TiO2 modified acrylic emulsion as raw material. The surface effect and quantum size effect of nano-TiO2 can also enhance the interaction between dye molecules and fibers, thereby improving the color fastness of printed fabrics. One end of the silane coupling agent is combined with the hydroxyl group on the surface of the nano-TiO2, and the other end is combined with the hydroxyl group or amino group and other functional groups on the fiber surface, thereby forming a firmly combined system. The doping of rare earth and the combination of the silane coupling agent KH-550 further enhance the color fastness of the printed fabric, including the color fastness to rubbing and the color fastness to washing. DETAILED DESCRIPTION

[0024] The technical scheme of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. It should be noted that raw materials can be obtained commercially, and the dyes in the embodiments of the present invention are all illustrated by taking disperse red HB as an example.

[0025] Example 1

[0026] This embodiment provides a printing liquid, comprising the following raw materials in parts by weight: 65 parts of modified acrylic emulsion, 2.2 parts of thickener, 1 part of dispersant, 4.5 parts of stabilizer, 0.75 parts of humectant, 1.5 parts of curing agent, 0.3 parts of defoaming agent, 4 parts of dye and 55 parts of water;

[0027] Wherein, the preparation method of the modified acrylic emulsion comprises:

[0028] (1) A method for preparing rare earth-doped nano-TiO2 comprises: dispersing silane coupling agent KH-550 in an ethanol aqueous solution by ultrasonic treatment for 130 minutes, adjusting the pH to 3.5 with glacial acetic acid to obtain a silane coupling agent solution; adding nano-TiO2 to anhydrous ethanol for ultrasonic dispersion for 60 minutes, adding cerium nitrate, and slowly dripping the silane coupling agent solution, adjusting the pH to 9.5 with ammonia water, heating to 70°C and stirring for reaction for 2.1 hours, cooling, centrifuging, washing with water, and drying at 60°C to obtain the product; the weight ratio of silane coupling agent KH-550, ethanol aqueous solution, nano-TiO2, anhydrous ethanol and cerium nitrate is 7:35:30:17.5:4.5; the mass ratio of water to ethanol in the ethanol aqueous solution is 1:1;

[0029] (2) Preparation of modified acrylic emulsion: acrylic acid, methyl methacrylate, n-butyl acrylate monomers are mixed with deionized water, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether are added and stirred to obtain a mixed solution, rare earth doped nano-TiO2 is then added for ultrasonic dispersion for 35 minutes, the temperature is gradually raised to 77°C, the pH is adjusted to 5, ammonium persulfate is added, the temperature is raised to 83°C, the temperature is kept for reaction for 4.5 hours, the temperature is lowered to room temperature, and the pH is adjusted to 8 with ammonia water; the weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, rare earth doped nano-TiO2 and ammonium persulfate is 2.5:13:21:45:0.75:1.1:0.3:4.5;

[0030] Among them, the thickener is ACRACONC FN 01; the dispersant is Dispers740W; the stabilizer is sodium citrate; the humectant is ethylene glycol; the curing agent is ARADUR38-1; and the defoaming agent is Z-2875.

[0031] The preparation method of the printing liquid comprises the following steps: adding defoamer, dispersant, moisturizer, stabilizer and water to modified acrylic emulsion in sequence while stirring, and stirring and dispersing; and then adding thickener, curing agent and dye, and stirring and dispersing evenly.

[0032] Example 2

[0033] This embodiment provides a printing liquid, comprising the following raw materials in parts by weight: 60 parts of modified acrylic emulsion, 2 parts of thickener, 0.5 parts of dispersant, 4 parts of stabilizer, 0.5 parts of humectant, 1 part of curing agent, 0.2 parts of defoaming agent, 3 parts of dye and 50 parts of water;

[0034] Wherein, the preparation method of the modified acrylic emulsion comprises:

[0035] (1) A method for preparing rare earth-doped nano-TiO2 comprises: dispersing silane coupling agent KH-550 in an ethanol aqueous solution by ultrasonic for 120 minutes, adjusting the pH to 3 with glacial acetic acid to obtain a silane coupling agent solution; adding nano-TiO2 to anhydrous ethanol for ultrasonic dispersion for 50 minutes, adding cerium nitrate, and slowly dripping the silane coupling agent solution, adjusting the pH to 9 with ammonia water, heating to 65°C and stirring for reaction for 2 hours, cooling, centrifuging, washing with water, and drying at 60°C to obtain the product; the weight ratio of silane coupling agent KH-550, ethanol aqueous solution, nano-TiO2, anhydrous ethanol and cerium nitrate is 6:30:25:15:4; the mass ratio of water to ethanol in the ethanol aqueous solution is 1:1;

[0036] (2) Preparation of modified acrylic emulsion: acrylic acid, methyl methacrylate, n-butyl acrylate monomers are mixed with deionized water, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether are added and stirred to obtain a mixed solution, rare earth doped nano-TiO2 is then added for ultrasonic dispersion for 30 minutes, the temperature is gradually raised to 75°C, the pH is adjusted to 4, ammonium persulfate is added, the temperature is raised to 82°C, the temperature is kept for 4 hours and then cooled to room temperature, and the pH is adjusted to 8 with ammonia water; the weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, rare earth doped nano-TiO2 and ammonium persulfate is 2:12:20:40:0.5:1:0.2:4;

[0037] Among them, the thickener is ACRACONC FN 01; the dispersant is Dispers740W; the stabilizer is sodium citrate; the humectant is urea; the curing agent is ARADUR3986; and the defoaming agent is Z-2875.

[0038] The preparation method of the printing liquid comprises the following steps: adding defoamer, dispersant, moisturizer, stabilizer and water to modified acrylic emulsion in sequence while stirring, and stirring and dispersing; and then adding thickener, curing agent and dye, and stirring and dispersing evenly.

[0039] Example 3

[0040] This embodiment provides a printing material liquid, comprising the following raw materials in parts by weight: 70 parts of modified acrylic emulsion, 2.4 parts of thickener, 1.5 parts of dispersant, 5 parts of stabilizer, 1 part of humectant, 2 parts of curing agent, 0.4 parts of defoaming agent, 5 parts of dye and 60 parts of water;

[0041] Wherein, the preparation method of the modified acrylic emulsion comprises:

[0042] (1) A method for preparing rare earth-doped nano-TiO2 comprises: dispersing silane coupling agent KH-550 in an ethanol aqueous solution by ultrasonic for 140 minutes, adjusting the pH to 4 with glacial acetic acid to obtain a silane coupling agent solution; adding nano-TiO2 to anhydrous ethanol for ultrasonic dispersion for 70 minutes, adding cerium nitrate, and slowly dripping the silane coupling agent solution, adjusting the pH to 10 with ammonia water, heating to 75°C and stirring for reaction for 2.2 hours, cooling, centrifuging, washing with water, and drying at 60°C to obtain the product; the weight ratio of silane coupling agent KH-550, ethanol aqueous solution, nano-TiO2, anhydrous ethanol and cerium nitrate is 8:40:35:20:5; the mass ratio of water to ethanol in the ethanol aqueous solution is 1:1;

[0043] (2) Preparation of modified acrylic emulsion: acrylic acid, methyl methacrylate, n-butyl acrylate monomers are mixed with deionized water, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether are added and stirred to obtain a mixed solution, rare earth doped nano-TiO2 is then added for ultrasonic dispersion for 40 minutes, the temperature is gradually raised to 79°C, the pH is adjusted to 6, ammonium persulfate is added, the temperature is raised to 84°C, the temperature is kept for reaction for 5 hours, the temperature is lowered to room temperature, and the pH is adjusted to 8 with ammonia water; the weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, rare earth doped nano-TiO2 and ammonium persulfate is 3:14:22:50:1:1.2:0.4:5;

[0044] Among them, the thickener is ACRACONC FN 01; the dispersant is Dispers740W; the stabilizer is sodium citrate; the humectant is glycerol; the curing agent is ARADUR38-1; and the defoaming agent is Z-2875.

[0045] The preparation method of the printing liquid comprises the following steps: adding defoamer, dispersant, moisturizer, stabilizer and water to modified acrylic emulsion in sequence while stirring, and stirring and dispersing; and then adding thickener, curing agent and dye, and stirring and dispersing evenly.

[0046] Example 4

[0047] This embodiment provides a printing liquid, comprising the following raw materials in parts by weight: 60 parts of modified acrylic emulsion, 2.4 parts of thickener, 0.5 parts of dispersant, 5 parts of stabilizer, 0.5 parts of humectant, 2 parts of curing agent, 0.2 parts of defoaming agent, 5 parts of dye and 50 parts of water;

[0048] Wherein, the preparation method of the modified acrylic emulsion comprises:

[0049] (1) A method for preparing rare earth-doped nano-TiO2 comprises: dispersing a silane coupling agent KH-550 in an ethanol aqueous solution by ultrasonic treatment for 140 minutes, adjusting the pH to 3 with glacial acetic acid to obtain a silane coupling agent solution; adding nano-TiO2 to anhydrous ethanol for ultrasonic dispersion for 70 minutes, adding cerium nitrate, and slowly dripping the silane coupling agent solution, adjusting the pH to 9 with ammonia water, heating to 75°C and stirring for reaction for 2 hours, cooling, centrifuging, washing with water, and drying at 60°C to obtain the product; the weight ratio of the silane coupling agent KH-550, the ethanol aqueous solution, the nano-TiO2, anhydrous ethanol and the cerium nitrate is 8:30:35:15:4; the mass ratio of water to ethanol in the ethanol aqueous solution is 1:1;

[0050] (2) Preparation of modified acrylic emulsion: acrylic acid, methyl methacrylate, n-butyl acrylate monomers are mixed with deionized water, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether are added and stirred to obtain a mixed solution, rare earth doped nano-TiO2 is then added for ultrasonic dispersion for 40 minutes, the temperature is gradually raised to 75°C, the pH is adjusted to 6, ammonium persulfate is added, the temperature is raised to 82°C, the temperature is kept for reaction for 5 hours, the temperature is lowered to room temperature, and the pH is adjusted to 8 with ammonia water; the weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, rare earth doped nano-TiO2 and ammonium persulfate is 2:14:20:50:0.5:1.2:0.2:5;

[0051] Among them, the thickener is ACRACONC FN 01; the dispersant is Dispers740W; the stabilizer is sodium citrate; the humectant is ethylene glycol; the curing agent is ARADUR38-1; and the defoaming agent is Z-2875.

[0052] The preparation method of the printing liquid comprises the following steps: adding defoamer, dispersant, moisturizer, stabilizer and water to modified acrylic emulsion in sequence while stirring, and stirring and dispersing; and then adding thickener, curing agent and dye, and stirring and dispersing evenly.

[0053] Comparative Example 1

[0054] This comparative example provides a printing material liquid, comprising the following raw materials in parts by weight: 65 parts of modified acrylic emulsion, 2.2 parts of thickener, 1 part of dispersant, 4.5 parts of stabilizer, 0.75 parts of humectant, 1.5 parts of curing agent, 0.3 parts of defoaming agent, 4 parts of dye and 55 parts of water;

[0055] Wherein, the preparation method of the modified acrylic emulsion comprises:

[0056] (1) A method for preparing rare earth-doped nano-TiO2 comprises: dispersing silane coupling agent KH-560 in an ethanol aqueous solution by ultrasonic for 130 minutes, adjusting the pH to 3.5 with glacial acetic acid to obtain a silane coupling agent solution; adding nano-TiO2 to anhydrous ethanol for ultrasonic dispersion for 60 minutes, adding cerium nitrate, and slowly dripping the silane coupling agent solution, adjusting the pH to 9.5 with ammonia water, heating to 70°C and stirring for reaction for 2.1 hours, cooling, centrifuging, washing with water, and drying at 60°C to obtain the product; the weight ratio of silane coupling agent KH-560, ethanol aqueous solution, nano-TiO2, anhydrous ethanol and cerium nitrate is 7:35:30:17.5:4.5; the mass ratio of water to ethanol in the ethanol aqueous solution is 1:1;

[0057] (2) Preparation of modified acrylic emulsion: acrylic acid, methyl methacrylate, n-butyl acrylate monomers are mixed with deionized water, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether are added and stirred to obtain a mixed solution, rare earth doped nano-TiO2 is then added for ultrasonic dispersion for 35 minutes, the temperature is gradually raised to 77°C, the pH is adjusted to 5, ammonium persulfate is added, the temperature is raised to 83°C, the temperature is kept for reaction for 4.5 hours, the temperature is lowered to room temperature, and the pH is adjusted to 8 with ammonia water; the weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, rare earth doped nano-TiO2 and ammonium persulfate is 2.5:13:21:45:0.75:1.1:0.3:4.5;

[0058] Among them, the thickener is ACRACONC FN 01; the dispersant is Dispers740W; the stabilizer is sodium citrate; the humectant is ethylene glycol; the curing agent is ARADUR38-1; and the defoaming agent is Z-2875.

[0059] The preparation method of the printing liquid comprises the following steps: adding defoamer, dispersant, moisturizer, stabilizer and water to modified acrylic emulsion in sequence while stirring, and stirring and dispersing; and then adding thickener, curing agent and dye, and stirring and dispersing evenly.

[0060] Comparative Example 2

[0061] This comparative example provides a printing material liquid, comprising the following raw materials in parts by weight: 65 parts of modified acrylic emulsion, 2.2 parts of thickener, 1 part of dispersant, 4.5 parts of stabilizer, 0.75 parts of humectant, 1.5 parts of curing agent, 0.3 parts of defoaming agent, 4 parts of dye and 55 parts of water;

[0062] Wherein, the preparation method of the modified acrylic emulsion comprises:

[0063] (1) A method for preparing rare earth-doped nano-TiO2 comprises: dispersing a silane coupling agent KH-570 in an ethanol aqueous solution by ultrasonic treatment for 130 minutes, adjusting the pH to 3.5 with glacial acetic acid to obtain a silane coupling agent solution; adding nano-TiO2 to anhydrous ethanol for ultrasonic dispersion for 60 minutes, adding cerium nitrate, and slowly dripping the silane coupling agent solution, adjusting the pH to 9.5 with ammonia water, heating to 70°C and stirring for reaction for 2.1 hours, cooling, centrifuging, washing with water, and drying at 60°C to obtain the product; the weight ratio of the silane coupling agent KH-570, the ethanol aqueous solution, the nano-TiO2, the anhydrous ethanol and the cerium nitrate is 7:35:30:17.5:4.5; the mass ratio of water to ethanol in the ethanol aqueous solution is 1:1;

[0064] (2) Preparation of modified acrylic emulsion: acrylic acid, methyl methacrylate, n-butyl acrylate monomers are mixed with deionized water, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether are added and stirred to obtain a mixed solution, rare earth doped nano-TiO2 is then added for ultrasonic dispersion for 35 minutes, the temperature is gradually raised to 77°C, the pH is adjusted to 5, ammonium persulfate is added, the temperature is raised to 83°C, the temperature is kept for reaction for 4.5 hours, the temperature is lowered to room temperature, and the pH is adjusted to 8 with ammonia water; the weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, rare earth doped nano-TiO2 and ammonium persulfate is 2.5:13:21:45:0.75:1.1:0.3:4.5;

[0065] Among them, the thickener is ACRACONC FN 01; the dispersant is Dispers740W; the stabilizer is sodium citrate; the humectant is ethylene glycol; the curing agent is ARADUR38-1; and the defoaming agent is Z-2875.

[0066] The preparation method of the printing liquid comprises the following steps: adding defoamer, dispersant, moisturizer, stabilizer and water to modified acrylic emulsion in sequence while stirring, and stirring and dispersing; and then adding thickener, curing agent and dye, and stirring and dispersing evenly.

[0067] Comparative Example 3

[0068] This comparative example provides a printing material liquid, comprising the following raw materials in parts by weight: 65 parts of modified acrylic emulsion, 2.2 parts of thickener, 1 part of dispersant, 4.5 parts of stabilizer, 0.75 parts of humectant, 1.5 parts of curing agent, 0.3 parts of defoaming agent, 4 parts of dye and 55 parts of water;

[0069] Wherein, the preparation method of the modified acrylic emulsion comprises:

[0070] (1) A method for preparing rare earth-doped nano-TiO2 comprises: dispersing silane coupling agent KH-550 in an ethanol aqueous solution by ultrasonic treatment for 130 minutes, adjusting the pH to 3.5 with glacial acetic acid to obtain a silane coupling agent solution; adding nano-TiO2 to anhydrous ethanol for ultrasonic dispersion for 60 minutes, slowly dripping the silane coupling agent solution, adjusting the pH to 9.5 with ammonia water, heating to 70°C and stirring for reaction for 2.1 hours, cooling, centrifuging, washing with water, and drying at 60°C to obtain the product; the weight ratio of silane coupling agent KH-550, ethanol aqueous solution, nano-TiO2 and anhydrous ethanol is 7:35:30:17.5; the mass ratio of water to ethanol in the ethanol aqueous solution is 1:1;

[0071] (2) Preparation of modified acrylic emulsion: acrylic acid, methyl methacrylate, n-butyl acrylate monomers are mixed with deionized water, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether are added and stirred to obtain a mixed solution, rare earth doped nano-TiO2 is then added for ultrasonic dispersion for 35 minutes, the temperature is gradually raised to 77°C, the pH is adjusted to 5, ammonium persulfate is added, the temperature is raised to 83°C, the temperature is kept for reaction for 4.5 hours, the temperature is lowered to room temperature, and the pH is adjusted to 8 with ammonia water; the weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, rare earth doped nano-TiO2 and ammonium persulfate is 2.5:13:21:45:0.75:1.1:0.3:4.5;

[0072] Among them, the thickener is ACRACONC FN 01; the dispersant is Dispers740W; the stabilizer is sodium citrate; the humectant is ethylene glycol; the curing agent is ARADUR38-1; and the defoaming agent is Z-2875.

[0073] The preparation method of the printing liquid comprises the following steps: adding defoamer, dispersant, moisturizer, stabilizer and water to modified acrylic emulsion in sequence while stirring, and stirring and dispersing; and then adding thickener, curing agent and dye, and stirring and dispersing evenly.

[0074] Comparative Example 4

[0075] This comparative example provides a printing material liquid, comprising the following raw materials in parts by weight: 65 parts of modified acrylic emulsion, 2.2 parts of thickener, 1 part of dispersant, 4.5 parts of stabilizer, 0.75 parts of humectant, 1.5 parts of curing agent, 0.3 parts of defoaming agent, 4 parts of dye and 55 parts of water;

[0076] Wherein, the preparation method of the modified acrylic emulsion comprises:

[0077] (1) A method for preparing rare earth-doped nano-TiO2 comprises: adding nano-TiO2 to anhydrous ethanol for ultrasonic dispersion for 60 minutes, adding cerium nitrate, adjusting the pH to 9.5 with ammonia water, heating to 70°C and stirring for reaction for 2.1 hours, cooling, centrifuging, washing with water, and drying at 60°C to obtain the product; the weight ratio of nano-TiO2, anhydrous ethanol and cerium nitrate is 30:17.5:4.5;

[0078] (2) Preparation of modified acrylic emulsion: acrylic acid, methyl methacrylate, n-butyl acrylate monomers are mixed with deionized water, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether are added and stirred to obtain a mixed solution, rare earth doped nano-TiO2 is then added for ultrasonic dispersion for 35 minutes, the temperature is gradually raised to 77°C, the pH is adjusted to 5, ammonium persulfate is added, the temperature is raised to 83°C, the temperature is kept for reaction for 4.5 hours, the temperature is lowered to room temperature, and the pH is adjusted to 8 with ammonia water; the weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, rare earth doped nano-TiO2 and ammonium persulfate is 2.5:13:21:45:0.75:1.1:0.3:4.5;

[0079] Among them, the thickener is ACRACONC FN 01; the dispersant is Dispers740W; the stabilizer is sodium citrate; the humectant is ethylene glycol; the curing agent is ARADUR38-1; and the defoaming agent is Z-2875.

[0080] The preparation method of the printing liquid comprises the following steps: adding defoamer, dispersant, moisturizer, stabilizer and water to modified acrylic emulsion in sequence while stirring, and stirring and dispersing; and then adding thickener, curing agent and dye, and stirring and dispersing evenly.

[0081] Comparative Example 5

[0082] This comparative example provides a printing material liquid, comprising the following raw materials in parts by weight: 65 parts of modified acrylic emulsion, 2.2 parts of thickener, 1 part of dispersant, 4.5 parts of stabilizer, 0.75 parts of humectant, 1.5 parts of curing agent, 0.3 parts of defoaming agent, 4 parts of dye and 55 parts of water;

[0083] Wherein, the preparation method of the modified acrylic emulsion comprises:

[0084] Acrylic acid, methyl methacrylate, n-butyl acrylate monomers are mixed with deionized water, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether are added and stirred continuously to obtain a mixed solution, nano-TiO2 is then added for ultrasonic dispersion for 35 minutes, the temperature is gradually raised to 77°C, the pH is adjusted to 5, ammonium persulfate is added, the temperature is raised to 83°C, the temperature is kept for reaction for 4.5 hours, then the temperature is lowered to room temperature, and the pH is adjusted to 8 with ammonia water to obtain the obtained solution; the weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, nano-TiO2 and ammonium persulfate is 2.5:13:21:45:0.75:1.1:0.3:4.5;

[0085] Among them, the thickener is ACRACONC FN 01; the dispersant is Dispers740W; the stabilizer is sodium citrate; the humectant is ethylene glycol; the curing agent is ARADUR38-1; and the defoaming agent is Z-2875.

[0086] The preparation method of the printing liquid comprises the following steps: adding defoamer, dispersant, moisturizer, stabilizer and water to modified acrylic emulsion in sequence while stirring, and stirring and dispersing; and then adding thickener, curing agent and dye, and stirring and dispersing evenly.

[0087] Comparative Example 6

[0088] This comparative example provides a printing material liquid, comprising the following raw materials in parts by weight: 65 parts of acrylic emulsion, 2.2 parts of thickener, 1 part of dispersant, 4.5 parts of stabilizer, 0.75 parts of humectant, 1.5 parts of curing agent, 0.3 parts of defoaming agent, 4 parts of dye and 55 parts of water;

[0089] Wherein, the preparation method of the acrylic emulsion comprises:

[0090] Acrylic acid, methyl methacrylate, and n-butyl acrylate monomers are mixed with deionized water, sodium dodecyl sulfate and nonylphenol polyoxyethylene ether are added, and stirring is continued to obtain a mixed solution, ultrasonic dispersion is performed for 35 minutes, the temperature is gradually raised to 77°C, the pH is adjusted to 5, and ammonium persulfate is added, the temperature is raised to 83°C, and the temperature is kept for reaction for 4.5 hours, then the temperature is lowered to room temperature, and the pH is adjusted to 8 with ammonia water. The weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether and ammonium persulfate is 2.5:13:21:45:0.75:1.1:4.5;

[0091] Among them, the thickener is ACRACONC FN 01; the dispersant is Dispers740W; the stabilizer is sodium citrate; the humectant is ethylene glycol; the curing agent is ARADUR38-1; and the defoaming agent is Z-2875.

[0092] The preparation method of the printing liquid comprises the following steps: adding defoamer, dispersant, moisturizer, stabilizer and water to acrylic emulsion in sequence while stirring, and stirring and dispersing; and then adding thickener, curing agent and dye, and stirring and dispersing evenly.

[0093] Test Example: The printing liquid prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-6 was used to print and dye fabrics, and the printed and dyed fabrics were subjected to the following tests:

[0094] Fabric apparent color depth: Fabric color depth is expressed as K / S value and is measured using SF600X Datacolor colorimeter;

[0095] Friction fastness test: Determined according to GB / T3920-2008 "Textile Color Fastness Test Friction Fastness". SF600X Datacolor colorimeter is used for determination and rating;

[0096] Soap fastness test: Determined according to GB / T3920-2008 "Textile Color Fastness Test-Rubbing Fastness". SF600X Datacolor colorimeter is used for determination and rating.

[0097] The results are shown in Table 1 below.

[0098] Table 1 Performance test

[0099]

[0100]

[0101] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A printing liquid, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of modified acrylic emulsion, 2-2.4 parts of thickener, 0.5-1.5 parts of dispersant, 4-5 parts of stabilizer, 0.5-1 parts of humectant, 1-2 parts of curing agent, 0.2-0.4 parts of defoaming agent, 3-5 parts of dye and 50-60 parts of water.

2. A printing liquid according to claim 1, characterized in that: The preparation method of the modified acrylic emulsion comprises: mixing acrylic acid, methyl methacrylate, n-butyl acrylate monomers with deionized water, adding sodium dodecyl sulfate and nonylphenol polyoxyethylene ether and continuing to stir to obtain a mixed solution, then adding rare earth-doped nano-TiO2 for ultrasonic dispersion for 30-40 minutes, gradually heating to 75-79°C, adjusting the pH to 4-6, then adding ammonium persulfate, heating to 82-84°C, keeping the temperature for reaction for 4-5 hours, then cooling to room temperature, and adjusting the pH to 8 with ammonia water to obtain the modified acrylic emulsion.

3. A printing liquid according to claim 2, characterized in that: The weight ratio of acrylic acid, methyl methacrylate, n-butyl acrylate monomer, deionized water, sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, rare earth doped nano-TiO2 and ammonium persulfate is (2-3): (12-14): (20-22): (40-50): (0.5-1): (1-1.2): (0.2-0.4): (4-5).

4. A printing liquid according to claim 2, characterized in that: The preparation method of rare earth doped nano TiO2 comprises: dispersing silane coupling agent KH-550 in ethanol aqueous solution by ultrasonic for 120-140 minutes, adjusting the pH to 3-4 with glacial acetic acid to obtain a silane coupling agent solution; adding nano TiO2 to anhydrous ethanol for ultrasonic dispersion for 50-70 minutes, adding cerium nitrate, slowly dripping the silane coupling agent solution, adjusting the pH to 9-10 with ammonia water, heating to 65-75°C, stirring for reaction for 2-2.2 hours, cooling, centrifuging, washing with water and drying to obtain the product.

5. A printing liquid according to claim 4, characterized in that: The weight ratio of the silane coupling agent KH-550, ethanol aqueous solution, nano-TiO2, anhydrous ethanol and cerium nitrate is (6-8): (30-40): (25-35): (15-20): (4-5).

6. A printing liquid according to claim 4, characterized in that: The mass ratio of water to ethanol in the ethanol aqueous solution is 1:

1.

7. A printing liquid according to claim 1, characterized in that: The thickener is ACRACONC FN 01; the dispersant is Dispers740W; and the stabilizer is sodium citrate.

8. A printing liquid according to claim 1, characterized in that: The moisturizing agent includes at least one of urea, ethylene glycol and glycerin; the curing agent includes ARADUR38-1 or ARADUR3986; and the defoaming agent is Z-2875.

9. A method for preparing a printing liquid as claimed in any one of claims 1 to 8, characterized in that the steps include: Add defoamer, dispersant, humectant, stabilizer and water to the modified acrylic emulsion in sequence while stirring, and disperse by stirring; then add thickener, curing agent and dye, and disperse by stirring evenly.

10. Use of the printing liquid according to any one of claims 1 to 8 in textile printing and dyeing.

Citation Information

Patent Citations

  • Environment-friendly dyeing agent for textile fabrics and preparation method thereof

    CN110424169A

  • Rare earth modified acrylic acid copolymerization water-based alkyd resin coating

    CN110577784A

  • Acrylic emulsion, preparation method thereof, water-based damping coating and application thereof

    CN117487063A

  • Anti-aging, high-reflection and high-emission fabric screen printing coating and preparation method thereof

    CN118087293A

  • Rare earth heat storage printing paste, preparation method thereof, finished fabric and application thereof

    CN118516870A